2015
DOI: 10.1021/acs.jpcc.5b02085
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Nonequilibrium Thermodynamic and Transport Properties of Ultrafast Laser Irradiated 316L Stainless Steel

Abstract: International audienceWe present calculations of transient behavior of thermodynamic and transport coefficients on the timescale of electron-phonon relaxation upon ultrashort laser excitation of ferrous alloys. Their role defining energy deposition and primary microscopic material response to the laser irradiation is outlined. Nonequilib-rium thermodynamic properties of 316L stainless steel are determined from first-principles calculations. Taking into account the complexity of multi-metallic materials, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…The energy conservation requires that ′ − = ℏΩ, and the electron-phonon spectral function is approximated as [9] 2 ( , ′ , )| = ( )| ( + ℏ )| 2 ( , , )| /[ ( )| ] 2 (5) Moreover, at the limit of ≫ ℏΩ and ≫ ℏΩ, the thermal factor becomes ( , ′ )| = [ ( ) − ( + ℏ )]( − ) /(ℏ ) (6) Because the energy range of electrons is much wider than that of phonons, ( ) is approximately equal to ( + ℏ ) and [ ( ) − ( + ℏ )]/(ℏ ) in Eq. (6), which can be rewritten as − ⁄ . In addition, at the high limit, the second moment of 2 ( )| is simplified as λ〈ω 2 〉| T e = 2 ∫ 2 ( )| ∞ 0…”
Section: Computational Detailsmentioning
confidence: 99%
“…The energy conservation requires that ′ − = ℏΩ, and the electron-phonon spectral function is approximated as [9] 2 ( , ′ , )| = ( )| ( + ℏ )| 2 ( , , )| /[ ( )| ] 2 (5) Moreover, at the limit of ≫ ℏΩ and ≫ ℏΩ, the thermal factor becomes ( , ′ )| = [ ( ) − ( + ℏ )]( − ) /(ℏ ) (6) Because the energy range of electrons is much wider than that of phonons, ( ) is approximately equal to ( + ℏ ) and [ ( ) − ( + ℏ )]/(ℏ ) in Eq. (6), which can be rewritten as − ⁄ . In addition, at the high limit, the second moment of 2 ( )| is simplified as λ〈ω 2 〉| T e = 2 ∫ 2 ( )| ∞ 0…”
Section: Computational Detailsmentioning
confidence: 99%
“…10, represent only the two-terminal cases. A continuum should exist between them, as determined by the degree of chemical partitioning, which we described previously [48], using a parameter, , being defined as the degree of chemical partitioning (12) This parameter is inversely related to chemical supersaturation as described in Ref. [48] in the liquid phase, as shown in Fig.…”
Section: Chemical Partitioning-temperature-phase Transformation (Cptpmentioning
confidence: 97%
“…The investigations by Fuerst et al [3] revealed that the magnetic field strength of melt spun Co-16 at.%Pr alloy composed of Co5Pr-D2d increases with wheel velocity, indicating the possible nonequilibrium phase transformation, i.e., percentage of the Co5Pr-D2d phase, increases (approaching 100%) with increasing wheel velocity. Recent, research efforts utilizing both experiments and theoretical calculations have examined new phases synthesis in nonequilibrium phase transformations from different angles such as using nonequilibrium reaction [4], composition effect on critical nucleation [5], critical cooling rate for amorphous formation [6], influence of rapid solidification on microstructure and thermodynamics [7], modeling dendrite growth under the local nonequilibrium condition [8], nonequilibrium dynamical mean-field theory [9], applying maximal entropy to multi-component stoichiometric compound growth [10], ab initio calculations coupled with the modified mixed-basis cluster expansion method [11], density functional theory phonon calculations [12], highentropy effects from nonequilibrium to equilibrium [13], the local nonequilibrium effects to the driving force for solidification [14] and structural enthalpy based on the modified Miedema's model [15]. The study of nonequilibrium phenomena has developed into one of the most active and exciting fields for material design, which can provide new insights beyond the equilibrium and theoretical understanding of the physics of phase selection.…”
Section: Introductionmentioning
confidence: 99%
“…This observation illustrates concepts involving the change of the localization degree of the electronic density upon laser heating of the electronic subsystem 15 . In these conditions, the material undergoes an electron-phonon nonequilibrium having consequences on thermodynamic and optical properties [15][16][17] , that modify in turn the energy deposition, storage and its further release. It also induces strong electronic pressures as well as nonthermal forces at very short time scales, having the potentiality to induce ultrafast phase transitions 4 or solid-to-solid transformations 5 .…”
Section: Introductionmentioning
confidence: 99%